Fatherlessness, Childhood Trauma, and Self-Harm in University Students: A Moderated Regression Analysis - Saudin, Efa; Rohmadani, Zahro Varisna (Utan Kayu Publishing, 2025)
Self-harm among university students has emerged as an increasingly urgent mental-health concern globally, yet research examining culturally specific risk mechanisms remains limited, particularly in Indonesian contexts where paternal roles are socially salient and emotional disclosure is often constrained. This study investigates whether childhood trauma moderates the association between fatherlessness and self-harm tendencies among late-adolescent university students. Using a quantitative correlational design, 123 participants completed validated measures of fatherlessness, childhood trauma, and self-harm. Data were analyzed using simple regression and Moderated Regression Analysis (MRA). Results indicated that fatherlessness positively predicts self-harm (β = 0.85, t = 17.75, p < .001) and childhood trauma is also strongly associated with self-harm (β = 0.65, t = 5.78, p < .001). More importantly, childhood trauma strengthened the positive relationship between fatherlessness and self-harm (interaction β = 0.14, t = 3.32, p = .001), demonstrating a quasi-moderation effect consistent with attachment disruption and developmental trauma frameworks. The final model explained 79.4% of the variance in self-harm, underscoring the combined role of paternal disengagement and early adversity in shaping students’ emotional vulnerability. These findings highlight the need for trauma-informed, family-aware mental-health services in higher-education settings, including early screening, psychoeducation, and resilience-building interventions for high-risk groups. Abstrak: Perilaku melukai diri pada mahasiswa telah menjadi isu kesehatan mental yang semakin mendesak secara global, namun kajian yang menelaah mekanisme risiko berbasis konteks budaya masih terbatas. Penelitian ini bertujuan untuk menguji apakah trauma masa kecil memoderasi hubungan antara kondisi tanpa sosok ayah (fatherlessness) dan kecenderungan melukai diri pada mahasiswa akhir remaja. Dengan menggunakan desain kuantitatif korelasional, sebanyak 123 partisipan mengisi instrumen terstandar mengenai fatherlessness, trauma masa kecil, dan perilaku melukai diri. Data dianalisis menggunakan regresi sederhana dan Analisis Regresi Moderasi (Moderated Regression Analysis/MRA). Hasil menunjukkan bahwa fatherlessness memprediksi perilaku melukai diri secara positif (β = 0.85, t = 17.75, p < .001) dan trauma masa kecil juga berasosiasi kuat dengan perilaku melukai diri (β = 0.65, t = 5.78, p < .001). Lebih jauh lagi, trauma masa kecil memperkuat hubungan positif antara fatherlessness dan perilaku melukai diri (β interaksi = 0.14, t = 3.32, p = .001), menunjukkan efek kuasi-moderasi yang konsisten dengan kerangka teori keterikatan dan trauma perkembangan. Model akhir menjelaskan 79.4% varians perilaku melukai diri, menegaskan peran gabungan keterlibatan ayah yang rendah dan pengalaman traumatis awal dalam membentuk kerentanan emosional mahasiswa. Temuan ini menekankan pentingnya layanan kesehatan mental berbasis trauma dan sensitif keluarga di lingkungan pendidikan tinggi, termasuk skrining dini, psikoedukasi, dan intervensi penguatan resiliensi bagi kelompok berisiko tinggi.